Redescobrindo espaços de esperanças: um resgate do sentimento topofílico nos ambientes escolares de Uberlândia - Marson, Noam Alves Martins (2016)
The knowledge of topophilia perception and cognitive processes that involve individuals inserted in multiple existing environments is an essential necessity for understanding the interrelationships with the space. However, can intervening in the environment, a relational product between subjects and their locations, influence the quality of life of both of them? Starting from the theoretical/practical interface between architecture and education, based on some schools historiography and their teaching experiences, and presenting the influence of the school building on the teaching-learning process, that question sought to be answered. Through the diagnosis of learning spaces in the context of Uberlandia, Minas Gerais, – specifically schools whose architectural design features the standard “H" model – and of its post-occupation, we sought to investigate the perception of its users, through methodological instruments of environmental quality evaluation. At this stage, it was primordial the (1) interview with the architect Paulo Carrara, author of the project whose building is taken as a research object; (2) the application of the walkthrough tour, which simultaneously combines the user interview and the environmental observation; and (3) the analysis of the wish poem, which reveals the children‟s perceptions of the natural elements existing in school through drawings. Based on these data, which reveal the technical condition of the school building, and also little understanding of their users for their potential attributes, it was possible to propose an architectural intervention, already concluding, that rescued, with its own architectural solution, the natural feeling of topophilia that permeates the individuals, categorizing schools as spaces of hope, the expected place to (re)construct a planetary environmental awareness.